Aroclor 1254 induced inhibitory effects on osteoblast differentiation in murine MC3T3-E1 cells through oxidative stress - Chen, Yu; Cai, Yuwei; Chen, Chunxiang; Li, Mengting; Lu, Lingdan; Yu, Zhongxiang; Wang, Shuqiang; Fang, Lei; Xu, Shengming (Frontiers in Endocrinology, 2022)
This study aimed to evaluate the osteotoxicity of polychlorinated biphenyls in murine osteoblastic MC3T3-E1 cells, and to explore the underlying mechanism focused on oxidative stress. The cells were exposed to Aroclor 1254 at concentrations of 2.5-20 µmol/L, and then cell viability, oxidative stress, intracellular calcium concentration, osteocalcin content, and calcium nodules formation were measured. Aroclor 1254 reduced cell viability and induced overproduction of intracellular reactive oxygen species in a dose-dependent manner. Activity of superoxide dismutase was decreased, and malondialdehyde content was promoted after exposure. Moreover, inhibitory effects of Aroclor 1254 on calcium metabolism and mineralization of osteoblasts were observed, as indicated by reduction of the intracellular calcium concentration, osteocalcin content, and modules formation rate. The decreased expression of osteocalcin, alkaline phosphatase, bone sialoprotein, and transient receptor potential vanilloid 6 further confirmed the impairment of Aroclor 1254 on calcium homeostasis and osteoblast differentiation. Addition of the antioxidant N-acetyl-L-cysteine partially restored the inhibitory effects on calcium metabolism and mineralization. In general, Aroclor 1254 exposure reduces calcium homeostasis, osteoblast differentiation and bone formation, and oxidative stress play a vital role in the underlying molecular mechanism of osteotoxicity.